Analisis Pelaksanaan Audit Kepatuhan Dana Kampanye Partai X Pada KAP Budiman Wawan Pamudji Dan Rekan - Muhammad Rafi Faisal; Hero Priono (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
The general election (Pemilu) is one of the essential elements in the administration of a democratic government and is a crucial moment when the people determine the direction of the nation. This research examines the performance of financial campaign compliance audits conducted by the Public Accountant Office (KAP) Budiman, Wawan, Pamji, and Partners X in cities A and B during the period 2023-2024. A qualitative research method with descriptive analysis is used to gain a deep understanding of the compliance audit process. Findings indicate that the constraints are caused by a lack of understanding among party officials regarding applicable regulations, human errors, and human resource limitations. This study highlights the need for integrated efforts to strengthen regulations, enhance supervision, and promote compliance with campaign finance regulations. Thus, elections are expected to be conducted cleanly, fairly, and honestly, strengthening the sovereignty and democracy of the Indonesian society.